Um lugar de memória para a Revolução Farroupilha: a construção do monumento a Bento Gonçalves da Silva em Porto Alegre 1934-1936 - Ramos, Luciano Braga (Universidade do Vale do Rio dos Sinos, 2015)
The intent of this paper is to search through different documents to perceive how the Bento Gonçalves da Silva monument was built in the mid-1930s in Porto Alegre, explain from the appropriation of the farroupilha memories by the historians and intellectuals from Rio Grande do Sul. I want to grasp how was built the "stage" for the rehabilitation of the gaucho memory, and, to realize how this fact contributed to build a place of memory from the Farroupilha Revolution in Porto Alegre. To do so I seek to verify how the formation of the imaginary Brazilian way of the gaucho came to be, based in a regional hallmark. I begin from the theoretical and intellectual level and, searching through political practices , I get to the materialization of the memory in the bronze from the monument to Bento Gonçalves da Silva. In the end what can be seen in the monument is a memory that is perpetuated, and in each conjuncture reinforces the idea of "heroism" by the gaucho in the adjustment of the collective memory, therefore fostering the collective imaginary of the people from Rio Grande do Sul around the Farroupilha Revolution history.
Keywords: Memória; Monumento; Comemoração; Lugar de memória; Memory; Monument; Celebration; Place of memory; ACCNPQ::Ciências Humanas::História